Analisis PDRB (Produk Domestik Regional Bruto) Dari Sisi Lapangan Usaha Provinsi Sumatra Utara - Mudrikah, Azizah; Maulidah, Aula; Jannah , Nurul (Rifa'Institute, 2021)
Gross Regional Domestic Product (GRDP) is the gross addedvalue (NTB) of all goods and services produced from a domesticarea arising from economic activity in a certain period regardlessof whether the production factors are owned by residents or nonresidents. This study aims to analyze the GRDP in North SumatraProvince from the side of the business field. This study uses adescriptive qualitative approach by using secondary data that isreviewed in the literature from various sources such as BPS(Central Statistics Agency), and Bank Indonesia as data analysisfor the Province of North Sumatra in the first quarter and thesecond quarter of 2021. This study looks at the existing variables.on Gross Domestic Product in terms of business fields. The resultsof the analysis of this research are the North Sumatran economybased on the amount of Gross Regional Domestic Product (GDP)based on current prices in the first quarter of 2021 reached Rp207.00 trillion and based on constant prices in 2010 reached Rp133.67 trillion. North Sumatra's economy in the second quarter of2021 compared to the previous quarter grew by 1.83% (q-to-q).